(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of malignancy in patients presenting with goiter undergoing for surgery. Study Design: An observational study. Place and Duration of Study: Surgical Department of Social Security Hospital Islamabad January 2002 to February 2011. Patients and Methods: All patients more than 10 years of age underwent thyroidectomy were included in the study. Postoperatively histopathologies of specimens were evaluated in all patients. Results: A total of 359 patients were operated and post operative histopathology specimens were reviewed. Eleven patients (3.06%) were having carcinoma. . Among all the thyroid carcinomas, papillary carcinoma was the commonest i.e. (45.45%, 5/11) followed by follicular carcinoma (27.27%, 3/11). Anaplastic carcinoma was seen in (18.18%, 2/11) and medullary carcinoma seen only in (9.09%, 1/11) Conclusion: Thyroid carcinoma is not an uncommon condition. Frequency of papillary carcinoma is very high in females among all the thyroid carcinoma